Eksperimen Penerapan Pembelajaran Berbasis Proyek (PJBL) pada Peningkatan Kreativitas Anak Usia Dini - Irayana, Ika; Assyauqi, Iqbal (JEA (Jurnal Edukasi AUD), 2024)
This article elucidates the significance of fostering creativity in early childhood through the implementation of the Project Based Learning (PJBL) model, particularly in the context of creativity. In an era of intensifying competition, Era 4.0 underscores the necessity for individuals to possess high creativity. Creativity is regarded as the pivotal factor in enhancing the quality of life of individuals and contributing to the prosperity of society. In the context of education, creativity plays a pivotal role in the early childhood learning process, given that every child possesses unique creative potential. The study employed a quasi-experimental design with experimental and control groups at PAUD Tarbiyatul Athfal UIN Antasari Banjarmasin, involving 36 children aged 4-6 years. Data were collected through checklist sheets and documentation of activities. The results demonstrated that the implementation of PPA significantly enhanced children's creativity in the experimental group. The Mann-Whitney U-Test analysis revealed a statistically significant difference between the two groups. Children who participated in PPA exhibited active engagement, collaborative skills, and proficiency in problem-solving, idea-sharing, and effective communication.